A truly Lego®-like modular microfluidics platform. (24th January 2017) - Vittayarukskul, Kevin; Lee, Abraham Phillip
Abstract: Ideally, a modular microfluidics platform should be simple to assemble and support 3D configurations for increased versatility. The modular building blocks should also be mass producible like electrical components. These are fundamental features of world-renowned Legos ® and why Legos ® inspire many existing modular microfluidics platforms. In this paper, a truly Lego ® -like microfluidics platform is introduced, and its basic feasibility is demonstrated. Here, PDMS building blocks resembling 2  ×  2 Lego ® bricks are cast from 3D-printed master molds. The blocks are pegged and stacked on a traditional Lego ® plate to create simple, 3D microfluidic networks, such as a single basket weave. Characteristics of the platform, including reversible sealing and automatic alignment of channels, are also analyzed and discussed in detail.